A mircostrip circuit tool kit app with FDTD analysis including lumped elements - Tan, Eng Leong (2015)
At the 2014 IEEE Microwave Theory and Techniques Society (MTT-S) International Microwave Symposium (IMS2014), the Apps for MTT Student Design Contest was held,sponsored by the Microwave Field Theory (MTT-15) Technical Committee. One objective of the design contest is to take advantage of the growing computing capacity of smart handheld and mobile devices to promote their use for the computer-aided analysis and design of microwave components and circuits. With the rapid development of recent iOS and Android smart phones or pads, some advanced scientific computation programs can now be executed on these portable devices. These handy devices can also deal with microwave circuit calculations if the applications (apps) are well designed. Since these devices are always accessible, it may be more convenient for engineers and students to analyze and design microwave circuits on the phones or pads directly. Note that full-wave, three-dimensional (3-D) simulations for complicated microwave circuits usually require a large amount of memory and a central processing unit with high performance, so it may be difficult to run full-wave 3-D simulations on portable smart devices.